2014
DOI: 10.5812/aapm.15546
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Electronic Learning and Lecture-Based Education in the Improvement of Interns’ knowledge About Advanced Cardiopulmonary Resuscitation Drug Pharmacology

Abstract: Background:Conventional educational systems seem to be improper throughout the cardiopulmonary resuscitation (CPR) teaching process. The most common causes of failed resuscitation are unfamiliarity with cardiopulmonary resuscitation algorithms, poor performance of leader of the CPR team and lack of skilled personnel, coordination among members during resuscitation, and responsibility of staff.Objectives:Electronic learning, as a new educational method is controversial issue in medical education for improving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Khoshbaten et al, concluded that both e-learning and lecture-based learning methods had the same results regarding the level of knowledge about CPR in general medicine students (interns) ( 11 ). The finding was in agreement with that of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khoshbaten et al, concluded that both e-learning and lecture-based learning methods had the same results regarding the level of knowledge about CPR in general medicine students (interns) ( 11 ). The finding was in agreement with that of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of e-learning is the access to all people everywhere in different locations ( 9 - 12 ). In fact, educational officials always focus on the effectiveness of e-learning on augmentation of students’ knowledge and attitudes ( 11 ). E-learning is a novel method in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies investigated OCDE in dentistry [ 39 , 45 ], whereas the rest investigated it in medicine, including 6 in surgery or anesthesia [ 37 , 47 , 48 , 50 , 51 , 54 ], 7 in internal medicine or family medicine [ 40 , 44 , 49 , 53 , 57 , 60 , 65 ], 5 in pediatrics [ 38 , 41 , 46 , 56 , 58 ], 3 in psychiatry [ 52 , 61 , 63 ], 1 in obstetrics and gynecology [ 42 ], and 1 in radiology [ 43 ]. In the 4 remaining trials, the subject of intervention was evidence-based medicine [ 55 ] or advanced life support [ 59 , 62 , 64 ]. We included 1 cRCT in this review [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the participants were trainees. In addition, 4 studies were conducted among 377 medical interns [ 55 , 62 - 64 ], 16 trials among a total of 686 postgraduate residents [ 37 , 42 , 44 , 46 - 50 , 52 , 54 , 58 - 61 , 65 ], and 1 study included 49 residents and faculty members [ 43 ], of the remaining studies, 7 were performed on 578 practicing doctors [ 39 - 41 , 45 , 53 , 56 , 57 ] ( Multimedia Appendix 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most e-learning interventions provide an online setup accessed with personal computers. However, our search did yield publications that reported offline approaches with personal computers in low- and lower-middle-income settings [23-26]. The reported methods resulted in varying levels of insights and also unveiled methods that needed adaption to yield evaluation results, such as the knowledge assessment with the student pretest that proved too easy, thus producing no knowledge nuances.…”
Section: Discussionmentioning
confidence: 99%